The Effect of Falou Application in Improving Students’ Speaking Skill - Lainatusshifa Saragih; Achmad Ramadhan; Ernita Daulay (Asosiasi Periset Bahasa Sastra Indonesia, 2024)
The research that has been conducted is entitled “The Effect of Falou Application in Improving Students’ Speaking Skill”, with the background being that the school want to implement English as the language in the school environment, but students’ speaking skill are still low. This research used quantitative methods with pre-test, treatment, and post-test design approaches in the experimental class and control class. The population in this study were students of class X Madrasah Aliyah Al – Washliyah Tebing Tinggi. This study used sample of two classes, namely experimental class as many as 30 students from X IPA-1 and control class as many as 30 students from X IPS-2. This study used a lottery method with random sampling style to select the sample. The validity processing tool used IBM Statistics Version 29. The result of this study revealed that there was a significant of using Falou Application in improving students’ speaking skill. This can be seen from the increase in the result of test, namely a Sig (2-tailed) value of 0.01 < 0.05 or t count (19.778) higher than t table (0.361). Based on the findings above, it can be concluded that the use of “Falou Application” has a significant effect on students’ speaking skill of Students in Madrasah Aliyah Al – Washliyah Tebing Tinggi.